Lack of repeat transduction by recombinant adeno-associated virus type 5/5 vectors in the mouse airway. - Sumner-Jones, S; Gill, DR; Hyde, S (2007)
While recombinant adeno-associated virus (rAAV) vectors promote long-term transgene expression in the lungs and other organs, the goal of correcting chronic inherited lung diseases such as cystic fibrosis with this type of viral gene transfer vector is limited by the requirement of achieving stable potent transgene expression, potentially requiring vector readministration. Here we evaluated the abilities of rAAV type 5/5 (rAAV5/5) vectors based on the genome and capsid of AAV5 to efficiently transduce the lungs and nasal epithelium of mice after repeated administration. Transduction efficiency as judged by reporter gene expression was markedly reduced on a second rAAV5/5 administration and effectively abolished on a third. Varying the period between administrations from 8 to 36 weeks did not allow efficient repeated administration. A rapid rise in anti-AAV5 antibodies was noted after rAAV5/5 vector administration that was sustained for the entire period of investigation (in some cases exceeding 9 months). Furthermore, this antibody response and subsequent failure to repeatedly administer the vector were not rescued by the in vivo expression of CTLA4Ig from an rAAV5/5 vector. These results suggest that without the development of an effective and clinically acceptable immunosuppression strategy, treatments for chronic diseases that require repeated administration of rAAV5/5 vectors will be unsuccessful.